Strategi Inovatif Manajemen Kesiswaan dalam Mengelola Disiplin Siswa melalui Tim Penegak di Sekolah Dasar - Izzah, Khoirotul; Magfiroh, Lailatul (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2025)
This research is motivated by the high value placed on discipline at SDI NU Pare, where every day, all members of the school community, including students, teachers, and staff, are taught, educated, and reminded about good and proper discipline in all aspects. Discipline is an attitude of adhering to orderliness through training, supervision, and habituation. Furthermore, innovation in student management, with the establishment of the Student Discipline Enforcement Team (TPDS), adds value to SDI NU Pare regarding student discipline, which must be shaped and instilled from the foundational level. The purpose of this research is to gain a deeper understanding of: 1) Student Management at SDI NU Pare, 2) Student Discipline Management at SDI NU Pare, and 3) The Student Discipline Enforcement Team as a Strategy in Student Management to manage student discipline. This research uses a qualitative case study approach to further explore student management and discipline management at SDI NU Pare. The findings of this study indicate that: 1) Student Management at SDI NU Pare is planned according to government policies and the foundation's guidelines, 2) Student discipline is highly valued and managed well and systematically, with effective and efficient planning, 3) The Student Discipline Enforcement Team serves as a relevant and effective strategy for managing student discipline, and in practice, it helps student management in disciplining undisciplined students and creating a conducive environment during teachers' meetings.